2009
DOI: 10.1016/j.juro.2009.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sinus Fat Invasion in pT3a Clear Cell Renal Cell Carcinoma Affects Outcomes of Patients Without Nodal Involvement or Distant Metastases

Abstract: Sinus fat invasion in clear cell renal cell carcinoma significantly affects cancer specific survival in patients without nodal or distant metastases. However, sinus fat invasion is not associated with worse cancer specific survival in cases of metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 12 publications
1
30
0
3
Order By: Relevance
“…Third, due to the number of cases, we were not able to demonstrate prognostic differences among histological subtypes (data not shown). Although the number of patients in our series is somewhat limited, it is similar to that in previous reports [9] and reflects the experience of a single tertiary-referral center. Furthermore, because of the rarity of locally advanced disease in the absence of metastatic disease [4] , few studies have focused on analyzing the outcome in this scenario.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Third, due to the number of cases, we were not able to demonstrate prognostic differences among histological subtypes (data not shown). Although the number of patients in our series is somewhat limited, it is similar to that in previous reports [9] and reflects the experience of a single tertiary-referral center. Furthermore, because of the rarity of locally advanced disease in the absence of metastatic disease [4] , few studies have focused on analyzing the outcome in this scenario.…”
Section: Discussionsupporting
confidence: 79%
“…In another study evaluating 365 patients with pT3a RCC (including those with metastatic disease), Margulis et al [18] found that, after adjusting for the effects of lymph node invasion and systemic metastases, sarcomatoid differentiation independently predicted the risk of death from cancer. In a more recent analysis, Bertini et al [9] evaluated 105 patients with pT3a RCC; an interesting finding of that study, as discussed by the investigators, was the independent role of sarcomatoid differentiation in CSS as it raised the risk of death by more than 5 times [9] . In agreement with these reports, our results suggest that the pathological evidence of sarcomatoid differentiation is one of the most important prognosticators, regardless of histological subtype, increasing the likelihood of cancer-related death by more than 3 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of this finding is controversial. Several authors believe that the presence of renal sinus fat invasion heralds a poorer prognosis compared with perinephric fat invasion [44,45]. However, Margulis et al [46] found no significant difference in outcomes.…”
Section: Variant: Renal Cell Carcinoma Stagingmentioning
confidence: 99%
“…But some tumors cannot be treated by nephron sparing surgery without compromising safety and oncological efficacy, due to a challenging central localization. Even small tumors in the central region may compromise the renal fat around the hilum and despite the low tumor volume, the possibility of a T3 should be considered and therefore RN may still be appropriate in this scenario (6). It has been reported that although experienced surgeons have similar outcomes with radical or partial nephrectomy (7,8), the partial approach can be technically challenging and associated with greater risk of complications, especially if done laparoscopically (9,10).…”
Section: Introductionmentioning
confidence: 99%